Emisi Gas CH4 dan CO2 serta Perubahan Kadar C-Organik pada Pengomposan Tandan Kosong Kelapa Sawit dan Rerumputan Menggunakan Bakteri Selulolitik Indigenous Pasang Surut - Nur, Hasrul Satria; Mawar, Silvia; Hadi, Abdul (Bioscientiae, 2025)
Oil palm empty bunch and grass, are sorts of agricultural waste, that contribute to evolving gas emissions--methane (CH4) and carbon dioxide (CO2).  Therefore, agricultural waste management to compost is one system to minimize the gas emissions in oil palm plantations.  Generally, using bio-decomposer lignocellulolytic bacterium is the way to speed up the composting.  Bacillus brevis BRT-1 and Bacillus megaterium BTB-1, having potency as bio-decomposer agents, are members of cellulolytic bacteria origin of soil swamps tidal.  Adding cellulolytic bacteria indigenous into the composting of oil palm empty bunch and grass are the objectives in our studies to observe, i.e. C-organic changes patterns, methane, and carbon dioxide emissions.  Two inoculants of cellulolytic bacteria comprised of BRT-1 and BTB-1 isolates were applied to the two substrates in composting the agricultural waste by adding cow manure.  The parameters of analysis were observed during twenty days, in addition, C-organic substrates were measured by the Walkley and Black method.  Especially for methane and carbon dioxide were observed by Micro Gas Chromatography, meanwhile, the addition of two inoculants of cellulolytic bacteria had a significant impact on C-organic changes during the composting.  Otherwise, using cellulolytic bacteria in this study showed no significant effect of methane and carbon dioxide.  Moreover, the result is also some of the depicted parameters, particularly of C-organic contain undergone alleviate on oil palm empty bunch substrates of BTB-1 – KS treatments.  Besides that, the C-organic content of grass substrates also decreased in BTB-1 treatments, furthermore, the methane emissions for oil palm empty bunch underwent fewer BRT-1+KS treatments.  On the other sides, the methane emissions increased during observation in grass substrates of BRT-1+KS treatments.  The same cases for the carbon dioxide emissions in oil palm empty bunch substrates are also decreased in BRT-1 treatments.  Meanwhile, the carbon dioxide emission underwent the escalation of grass substrates in BRT-1+KS treatments.  The utilization of cellulolytic bacteria Indigenous has the potential as a bio-decomposer agent in composting especially in accelerating C-organic changes.